Cognitive decline among older adults with heart diseases before and during the COVID-19 pandemic: A longitudinal cohort study - Hua, Rong; Li, Chenglong; Gao, Darui; Zheng, Fanfan; Xie, Wuxiang (Frontiers in Cardiovascular Medicine, 2023)
Background: Little is known about the impact induced by the COVID-19 pandemic in cognitive function on older adults with heart diseases. This study aimed to examine whether older adults with heart diseases suffered larger cognitive deterioration during the COVID-19 pandemic. Methods: This study leveraged longitudinal data from the Health and Retirement Study (HRS), a nationally representative US ageing cohort with objective cognitive assessments measured before and during the pandemic. The interval from HRS waves 13 to 14 (April 2016 to June 2019) was defined as the pre-pandemic period to control the pre-existed cognitive difference between participants with and without heart diseases, the interval from waves 14 to 15 (June 2019 to June 2021) was defined as the pandemic period. HRS survey wave 14 was considered as the baseline. The heart diseases status was defined by self-reported diagnosis. Linear mixed models were performed to evaluate and compare the cognitive differences during different periods. Results: 9304 participants (women: 5655, 60.8%; mean age: 65.8 ± 10.8 years) were included, 2119 (22.8%) had heart diseases. During the pre-pandemic period, there was no significant difference (-0.03, 95% CI: -0.22 to 0.15, P=0.716) in the changes of global cognitive scores between participants with and without heart diseases. During the pandemic period, a larger decreased change in global cognitive score was observed in heart diseases group compared with non-heart diseases group (-0.37, 95% CI: -0.55 to -0.19, P<0.001). An enlarged difference in global cognitive score was observed during the pandemic period (-0.33, 95% CI: -0.65 to -0.02, P=0.036). Conclusions: The findings demonstrated that heart diseases population suffered more cognitive decline induced by the pandemic, underscoring the necessity to provide immediate cognitive monitoring and interventions for heart diseases population.